IMPLEMENTASI MATERI PRODUKSI PADA IKLAN LAYANAN MASYARAKAT “Kita Indonesia” - Ichsan Widi Utomo; Christopher Yudha Erlangga (JIKE: Jurnal Ilmu Komunikasi Efek, 2019)
This study seeks to implement appropriate production management in the production of "Kita Indonesia" public service advertising produced by the broadcasting study program of the University of Bina Sarana Informatika communicating with the Ministry of Home Affairs of the Republic of Indonesia. In this production special production theories are applied that are in accordance with the concept of production of public service advertising. This production is different from the production of television programs related to no drama but does not cover estimation Production material can be used in the production of community service advertisements "Kita Indonesia", although not in the television program category. Keywords: Production Management, Productions Materials, Public Service Ads